A pandemia da covid-19 e a virtualização das manifestações culturais no município de Manaus: entre o vivido e o virtual - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
The Covid-19 pandemic, which began in Wuhan, China in 2019, has led to a global public health crisis. Despite scientific advances, the pandemic has left many workers adrift. The WHO's declaration of a pandemic in March 2020 led to social isolation measures. The economic crisis has exacerbated the exploitation of the workforce, especially in countries with less consolidated structures. Mészáros, in discussing the destructive power of capital, highlights the socio-metabolic system of capital, highlighting the metabolic exchange between humanity and nature. This dissertation is an ethnographic work that stems from a practical research experience as well as a reflective and theoretical process on the Covid-19 pandemic and the virtualization of cultural manifestations in the municipality of Manaus: Between the lived and the virtual, based on the limits and potential of the use of digital technologies in the interaction of the Manaus artistic class in the face of the pandemic. The field research was carried out with artists in different artistic segments, more specifically singers working in the city who, during the period of social isolation, were forced to reinvent themselves and find new ways of connecting with their audience. Faced with this social reconfiguration caused by the virus, artists have become virtually literate in order to keep their cultural manifestation alive. The research shows that the challenges have been significant. Virtuality can provide new opportunities, but the absence of face-to-face contact has brought losses, affecting the aesthetic and emotional experience of some spectators. However, the artists' resilience and creativity allowed them to overcome these challenges, reconstituting their practices and exploring new forms of expression, although challenging, opened up new paths for art and culture in the digital age.
Keywords: Artistas - Manaus (AM); Letramento digital; COVID-19, Pandemia de, 2020-; CIENCIAS SOCIAIS APLICADAS; Covid-19; Manifestação cultural; Artistas manauaras; Letramento digital